La conformità della volontà umana con quella divina nella Somma Teologica di San Tommaso d’Aquino (seconda parte) - Mestre, Alberto (Alpha omega, 2019)
In what way can the human will be conformed with the divine Will? That isthe subject of this article. The inquiry focuses primarily on St. Thomas Aquinas’ Summa Theologiae, Ia-IIae, quaestio 19, a question that specifically concerns the subject from a moralperspective. Is it possible that man would dare to make such a claim? If it is possible, how could it be brought about? The article traces the footsteps of St. Thomas, who faces this problem, well aware of the enormous importance it represents, and also aware that we standbefore one of the greatest mysteries of human and Christian life.